2001
DOI: 10.2214/ajr.177.2.1770325
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Duration of Pain and Secondary Signs of Obstruction of the Urinary Tract on Unenhanced Helical CT

Abstract: All CT secondary signs of ureteral obstruction except nephromegaly showed a significant increase in frequency as duration of flank pain increased. This observation may explain why the CT studies of some patients with acute ureterolithiasis show negative findings for some or all CT secondary signs of obstruction. Therefore, knowledge of the duration of pain is important when interpreting unenhanced CT studies in patients with acute ureterolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 14 publications
1
50
1
9
Order By: Relevance
“…2 Lastly, obstructing stones may be associated with a longer duration of pain. 6 In the absence of absolute indications for acute intervention, such as signs of urinary tract infection (UTI), renal failure, or unrelenting pain, there remains uncertainty as to whether patients presenting with unilateral obstructing calculi can be treated conservatively or warrant more prompt urological management. Our study aimed to determine whether unilateral, obstructing ureteric calculi identified on computed tomography (CT) at the time of renal colic presentation in the ED, independent of other factors, was associated with an increased likelihood of urological intervention.…”
Section: Introductionmentioning
confidence: 99%
“…2 Lastly, obstructing stones may be associated with a longer duration of pain. 6 In the absence of absolute indications for acute intervention, such as signs of urinary tract infection (UTI), renal failure, or unrelenting pain, there remains uncertainty as to whether patients presenting with unilateral obstructing calculi can be treated conservatively or warrant more prompt urological management. Our study aimed to determine whether unilateral, obstructing ureteric calculi identified on computed tomography (CT) at the time of renal colic presentation in the ED, independent of other factors, was associated with an increased likelihood of urological intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect, by order of frequency, include: hydroureter, hydronephrosis, striation of the perirenal fat, homolateral increase in the renal size, visible ureteral wall around the calculus (halo sign) and periureteral heterogeneity adjacent to the calculus (1,11,12) . Some of these secondary signs may be present in patients without a disease caused by ureteral calculus (12) , may be precociously absent, and may become more noticeable with time (13) . Other more recently described secondary findings are: unilateral absence of a hyperdense medullary pyramid (11) and decrease in attenuation of an acutely obstructed renal parenchyma in comparison with the contralateral kidney (14) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have nullified eventual differences resulting from prostatic enlargement in elderly men with vesical floor elevation, alterations in the pelvic floor level resulting from parturition, and anaof uric acid, with densities ranging between 300 and 400 UH (8) . Only exceptions are calculi resulting from deposition of protease inhibitors (Indinavir), which should be taken into consideration in patients undergoing treatment for the human immunodeficiency syndrome and with indirect renal calyceal system obstructive signs (11,13) . Studies performed since Smith et al (6) , in 1995, have found negative predictive values between 91% and 100%, positive predictive values between 96% and 100%, sensitivity between 95% and 100%, and specificity between 92% and 100%, for detection of ureteral calculi with unenhanced helical CT (4) , with excellent reproducibility, independently from the radiologist experience (1,9) .…”
Section: Discussionmentioning
confidence: 99%
“…Direct stone identification is diagnostic for lithiasis, but a stone may not be easily identified due to its small size, low attenuation, respiratory movement artifacts, inadequacy of retroperitoneal fat tissue, phleboliths, and recent stone passage; under these circumstances, the presence of secondary signs carries great importance for prediction of the duration of stone disease and its management (37,38). The secondary signs include asymmetric perinephric fat stranding, dilatation of the intrarenal collecting system, hydroureter, tissue rim sign, unilateral renal enlargement and pale kidney, and unilateral absence of white renal pyramids.…”
Section: Secondary Findingsmentioning
confidence: 99%